Analisis Faktor Keberhasilan Usaha pada Wirausahawan Mahasiswa dan Alumni di Perguruan Tinggi - Nurul, Ari Nurul Fatimah; Astutik, Erni Puji; Surytimur, Kartika Pradana; Priyono, Nuwun; Panggiarti, Endang Kartini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Many college alumni prepare themselves to look for job vacancies rather than preparing to create entrepreneurship. The aim of this research is to explain the success factors of student and alumni entrepreneurs in higher education. Quantitative research is a research design whose source is primary data. The data comes from a questionnaire distribution. Samples were obtained from students and alumni who had taken entrepreneurship courses at the university. Data analysis was carried out using validity and reliability tests to test the questionnaire, while hypothesis testing was carried out using the classic assumption test. After processing the data, the results are that capital variables, social networks, business income, and infrastructure have an influence on business success. Other variables, namely business management training and university support, have no effect on business success.